Front Cover: Breast Milk‐Derived Limosilactobacillus reuteri Prevents Atopic Dermatitis in Mice via Activating Retinol Absorption and Metabolism in Peyer's Patches. Issue 2 (20th January 2023) - Qi, Ce; Tu, Huayu; Zhao, Yuning; Zhou, Jingbo; Chen, Jie; Hu, Haiting; Yu, Renqiang; Sun, Jin
Abstract : Mol. Nutr. Food Res . 2023, 67, 202200444 DOI: 10.1002/mnfr.202200444 Limosilactobacillus reuteri Fn041 is a breast milk‐derived probiotic from agricultural and pastoral areas. Eczema is prevented in mice pups when Fn041 is administrated to dams during later pregnancy and lactation and to pups after weaning. The mechanism is related to the promotion of retinol absorption and conversion to retinoic acid in Peyer's patches, which is critical for oral tolerance development. This is reported by Renqiang Yu, Jin Sun, and co‐workers in article number 2200444 .